Pengembangan Sistem Informasi Administrasi Badan Usaha Milik Desa (BUMDesa) pada Desa Kareka Nduku Induk Kabupaten Sumba Barat dengan Metode Rapid Application Development - Astuti Rangu; Adelbertus Umbu Janga; Paulus Mikku Ate (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Village-Owned Enterprises (BUMDes) are regulated in Article 1 Paragraph (6) of the Regulation of the Minister of Home Affairs Number 39 of 2010, which states that BUMDes is a business formed by the village government with its ownership and management involving the village government and the community. BUMDesa Kareka Nduku, although it functions as a village economic empowerment institution, faces a number of challenges in its operations. Some of the main problems faced are difficulties in recording agricultural assets and tools, as well as the insynchronization between stock records in warehouses and records in the treasurer, which leads to frequent shortages of fertilizer and insecticide stocks. In addition, the manual recording process for capital and business loans causes the creation of monthly reports to take a long time, even more than an hour, and there are often errors because officers have to check daily reports from various fields. This resulted in delays in making reports that should have been submitted by the BUMDes.